Multiculturalismo alla francese? - Dino, Costantini (Strumenti per la didattica e la ricerca, 2009)
In theory, republican orthodoxy does not acknowledge the political dignity of any intermediary body between free and equal individuals, stripped of all particularism, and the sovereign nation. This is why, right up to the present, the French public debate has been marked by an entrenched suspicion towards all forms of «communitarism», and by the proscription of the very concept of multicultural politics. But have the policies actually pursued by republican France been consistent with the proclaimed principles? Is it genuinely possible to claim that cultural identities have never been publicly «recognised»? This multidisciplinary investigation proposes to address the ambiguous relations between theory and practice in the Republican management of cultural pluralism.